DAMPAK PENERAPAN METODE NUMBERED HEADS TOGETHER TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA [THE IMPACT OF THE IMPLEMENTATION OF THE NUMBERED HEADS TOGETHER METHOD ON STUDENTS' MATHEMATICAL CONCEPTUAL UNDERSTANDING] - Gidion Indra Saputra; Melda Jaya Saragih (Polyglot, 2021)
One of the objectives of learning mathematics is to develop students' understanding of mathematical concepts to be able to solve math problems. In mathematics learning, understanding concepts is very important because by understanding concepts students can learn higher order thinking skills. However, through a test at the observation stage, the researchers found that students had difficulty understanding mathematical concepts. The purpose of this study was to see whether the application of the Numbered Heads Together method influences students’ understanding of mathematical concepts. The research was conducted on 32 seventh grade students at Rantepao Christian Junior High School using qualitative descriptive research. Data sources in this study include student work results, mentor observation sheets, tests, and researcher reflection journals. The results of the study show that the application of the Numbered Heads Together method can help develop students' understanding of the mathematical concept.BAHASA INDONESIA ABSTRACT: Salah satu tujuan dari pembelajaran Matematika adalah mengembangkan pemahaman konsep matematik siswa untuk dapat menyelesaikan masalah Matematika. Dalam pembelajaran Matematika, memahami konsep sangat penting karena dengan memahami konsep Matematika siswa dapat mempelajari ketrampilan berpikir yang lebih tinggi. Namun, melalui test pada tahap observasi, peneliti menemukan bahwa siswa mengalami kesulitan dalam memahami konsep Matematika. Tujuan penelitian ini adalah untuk melihat dampak penerapan metode Numbered Heads Together terhadap pemahaman konsep matematis siswa. Penelitian dilakukan kepada 32 siswa kelas VII di SMP Kristen Rantepao dengan menggunakan jenis penelitian deskriptif kualitatif. Sumber data dalam penelitian ini antara lain: hasil pekerjaan siswa, lembar observasi mentor, tes, dan jurnal refleksi peneliti. Hasil penelitian menunjukkan bahwa penerapan metode Numbered Heads Together dapat membantu mengembangkan pemahaman konsep matematis siswa.